On How Fas Apoptosis-Independent Pathways Drive T Cell Hyperproliferation and Lymphadenopathy in lpr Mice - Balomenos, Dimitrios; Shokri, Rahman; Daszkiewicz, Lidia; Vázquez-Mateo, Cristina; Martínez-A, Carlos (Frontiers in Immunology, 2017)
Fas induces massive apoptosis in T cells after repeated in vitro TCR stimulation, and is critical for lymphocyte homeostasis in Fas-deficient (lpr) mice. Although the in vitro Fas apoptotic mechanism has been defined, there is a large conceptual gap between this in vitro phenomenon and the pathway that leads to in vivo development of lymphadenopathy and autoimmunity. A striking abnormality in lpr mice is the excessive proliferation of CD4+ and CD8+ T cells, and more so of the double-negative (DN) TCR+CD4-CD8-B220+ T cells. The basis of lpr T cell hyperproliferation remains elusive, as it cannot be explained by Fas-deficient apoptosis. T cell-directed p21 overexpression reduces hyperactivation/hyperproliferation of all lpr T cell subtypes and lymphadenopathy in lpr mice. p21 controls expansion of repeatedly stimulated T cells without affecting apoptosis. These results confirm a direct link between hyperactivatio/hyperproliferation, autoreactivity and lymphadenopathy in lpr mice and, with earlier studies, suggest that Fas apoptosis-independent pathways control lpr T cell hyperproliferation. lpr T cell hyperproliferation could be an indirect result of the defective apoptosis of repeatedly stimulated lpr T cells. Nonetheless, in this perspective we argue for an alternative setting, in which lack of Fas would directly cause lpr T cell hyperactivation/hyperproliferation in vivo. We propose that Fas/FasL acts as an activation inhibitor of recurrently stimulated T cells, and that its disruption causes overexpansion of T cells in lpr mice. Research to define the underlying mechanism of this Fas/FasL effect could resolve the phenotype of lpr mice and lead to therapeutics for related human syndromes.